A comparison of interval division methods in adaptive IEEE 802.11p–based multi-channel medium access control protocols for vehicular ad hoc networks. (February 2019) - Nguyen, VanDung; Oo, Thant Zin; Khanh, Tran Trong; Hong, Choong Seon; Huh, Eui-Nam
Recently, vehicular ad hoc networks, which organize communications between vehicles and between vehicles and infrastructures, have played an important role in providing safe transportation and infotainment applications. To satisfy the various requirements of applications such as delay-bounded transmission of safety packets, a broad bandwidth of non-safety packets, known as medium access control has been developed. In addition, to cope with the frequent topology changes of vehicular ad hoc networks, adaptive IEEE 802.11p–based multi-channel medium access control protocols have been proposed, which can adapt to different traffic conditions. In this article, we focus on such protocols and classify them according to interval division methods. Here, we perform comparisons between these protocols following three main categories: the fixed safety transmission interval, safety and Wireless Access in Vehicular Environment Service Advertisement/Acknowledgment transmission interval, and safety and Wireless Access in Vehicular Environment Service Advertisement transmission interval. We performed simulations in NS-3 under the assumption of saturated throughput for Wireless Access in Vehicular Environment Service Advertisement packets and a Poisson arrival process for the safety packets. From the simulation results, it is evident that the design of a new multi-channel medium access control protocol based on IEEE 802.11p needs to balance the trade-off between transmission delay and packet delivery ratio to be efficient, reliable and adaptive. Moreover, such a medium access control protocol can provide efficient vehicle-to-vehicle and vehicle-to-infrastructure communications, which affect the stability of the vehicular cloud.